UJI EKSTRAK BAGIAN UMBI BAWANG MERAH TERHADAP JAMUR Magnaporthe grisea - Hangger Gahara Mawandha (Program Studi Agroteknologi INSTIPER, 2017)
Shallot is widely consumed components of the diet of many populations, particularly in Asian diets. It is widely believed to be beneficial to health and even curative potential against a range of debilitating conditions and diseases. Allelochemical analysis of shallot extracts has confirmed the presence of some compound that inhibit of fungi activities. In the present study to know a part of shallot that suppress of Magnaporthe grisea activities and for knowing effective concentration that suppress of Magnaporthe grisea activities. Allelochemical compounds isolated from three parts of the tuber, skin, and discs of shallot. Separation of antifungal compounds with the addition of hexane, MeOH 70%, and butanol. Purification of compounds on any part of the shallot is done by evaporation method. Once evaporated, then add 80% ethanol and wind dried. Compounds derived from tuber, skin, and discs of shallot tested against Magnaporthe grisea. The extract concentration a part of shallot tested was 100 µg/ml, 200 µg/ml, and 500 µg/ml and aquades for controller. The result showed that discs of shallot with concentration of 500 µg/ml could suppress of Magnaporthe grisea activities, which reached 42%. The procentage was the highest suppress of Magnaporthe grisea activities than another part of shallot and another concentration, but the procentage still less than 50%. However, using all parts of the shallot with a concentration of 500 µg/ml would be more effective in suppressing the activity of Magnaporthe grisea.